Skema Bisnis Beautypreneur dengan SWOT Analysis dan Business Model Canvas (BMC) pada LW Beauty - Moch. Mahmudi Rosid; Dessy Srikandi; Chandra Kirana (JURNAL INDUSTRI DAN TEKNOLOGI SAMAWA, 2026)
The beauty industry market in Indonesia is experiencing significant growth, with an annual growth prediction of 4.73% until 2030. LW Beauty SMEs in Nganjuk, since February 2025, have been offering facials, anti-aging treatments, skincare, and mom-baby spa services, still operating their business with semi-conventional methods, thus requiring a business model that is adaptive, directed, and tactical according to current trends. This study integrates SWOT Analysis and Business Model Canvas (BMC) to formulate business strategies. The results yielded tactical strategies tailored to LW Beauty's capabilities. Business strategies that can be implemented include collaborating with influencers/government for education and promotion, recruiting freelancers as digital admins, offering special promotions for students, creating a digital community, and utilizing marketplaces to increase revenue